Re-evaluating the Relationship between Prenatal Employment and Birth Outcomes: A Policy-Relevant Application of Propensity Score Matching - Kozhimannil, Katy Backes (2012)
BACKGROUND: Prior research shows an association between prenatal employment characteristics and adverse birth outcomes but suffers methodological challenges in disentangling women’s employment choices from birth outcomes, and little U.S.-based prior research compares outcomes for employed women with those not employed. This study assessed the effect of prenatal employment status on birth outcomes. METHODS: With data from the Listening to Mothers II survey, conducted among a nationally representative sample of women who delivered a singleton baby in a U.S. hospital in 2005 (N=1,573), we used propensity score matching to reduce potential selection bias. Primary outcomes were low birth weight (< 2,500 grams) and preterm birth (gestational age < 37 weeks). Exposure was prenatal employment status (full-time, part-time, not employed). We conducted separate outcomes analyses for each matched cohort using multivariable regression models. FINDINGS: Comparing full-time employees with women who were not employed, full-time employment was not causally associated with preterm birth (adjusted odds ratio AOR = 1.37, p = 0.47) or low birth weight (AOR = 0.73, p = 0.41). Results were similar comparing full- and part-time workers. Consistent with prior research, black women, regardless of employment status, had increased odds of low birth weight compared with white women (AOR = 5.07, p =0.002). CONCLUSIONS: Prenatal employment does not independently contribute to preterm births or low birth weight after accounting for characteristics of women with different employment statuses. Efforts to improve birth outcomes should focus on the characteristics of pregnant women (employed or not) that render them vulnerable.